Low- or high-dose preventive aspirin use and risk of death from all-cause, cardiovascular disease, and cancer: A nationally representative cohort study - Chen, Yu; Chen, Fuli; Liao, Jie; Han, Hukui; Li, Gang; Zhou, Long (Frontiers in Pharmacology, 2023)
Background and aim: For a long time, aspirin has been recommended for the prevention of cardiovascular disease (CVD). However, results of long-term effects of aspirin use on the risk of CVD and all-cause death as well as cause-specific mortality are not consistent. This study aims to investigate the relationship between low- or high-dose preventive aspirin use and the risk of death from all-cause, CVD, and cancer among US adults aged 40 years and older. Methods: A prospective cohort study was conducted by utilizing four cycles of the National Health and Nutrition Examination Survey (NHANES) and linked 2019 mortality files. Cox proportional hazard models accounting for multiple covariates were used to calculate hazard ratio (HR) and 95% confidence interval (CI) for the associations between low- or high-dose aspirin use and risk of death. Results: A total of 10,854 individuals (5,364 men and 5,490 women) were enrolled in the study. During a median follow-up of 4.8 years, 924 death events including 294 CVD death and 223 cancer death were documented. We found no evidence that taking low-dose aspirin decreased the chance of dying from any cause (HR: 0.92, 95% CI: 0.79–1.06), CVD (HR: 1.03, 95% CI: 0.79–1.33), or cancer (HR: 0.80, 95% CI: 0.60–1.08). High-dose aspirin users had a higher risk of CVD death compared to participants who had never used aspirin (HR: 1.63, 95% CI: 1.11–2.41). Conclusion: Using low-dose aspirin has no effect on the risk of death from any causes, whereas taking high doses of aspirin increases the risk of CVD death.